Viela das flores na Vila Missionária: as escrevivências de um território violentado pelo estado e a configuração da subjetividade - Lima, Thaís Fernanda Gonçalves de (2021)
This research have for aim show how the state violence, by the police violence, is present in the life of the youth and their families in the periphery, especially in the life of the youth, of the mothers and the residents of Viela das Flores, in the neighborhood of Vila Missionario, where the author grow up and see the police killing the young people that live there. The author presents one analysis about the importance of the movement of brazilians mothers who fight to incriminate the state for the extermination of the black, poor and peripheric youth. And the feelings that surrounded her, in the pain in common with the saying “to pain to fight”. The methodology used in this research was the “escrevivências” by the writer Conceição Evaristo. She analysed, using the registers named “escrevivências de campo” , which feelings run through mothers, young people and residents in the territory in which police violence, structural racism, social inequality, precariousness of culture and leisure. From the analysis made in that research it can be concluded that the collectivity present in the peripheric territory offers more protection to the youth, their mothers and families, but that isn't enough for the state to not exterminate their children, brothers and neighbours. She concluded that it is needed that discomfort happens in Brazilian society, to stand against the violence that often happens to people who live in the periphery territory. The recognition of structural racism goes through the perception that, to fight the extermination plan of the state, it is needed to be a fight for the whole society and not a try, protection and fight of the mothers, the residents of these neighborhoods, where the violence of the state and police is present. Is needed that the public policy be built so that the Brazilian youth have the life guaranteed. This is needed that structural racism be fought and the right to live of the youth be made effective from the opportunity to build life projects, accessing opportunities in the periphery